Aspek Hukum Kartu Kredit dan Dilema Penagihannya - Sihombing, Jonker (Pelita Harapan University, 2011)
Credit card is used by holder or consumer to pay bills or to withdraw money in case of needs. In order to get a credit card, consumer should file an application to the issuer ( usually bank ), and then issuer will give approval on it. Terms and condtions of the card is set standard and designed solely by the issuer. This standardized clause is considered as a âtake it or leave it contractâ, which couldnât be avoided by holder. Act No. 8 of 1999 regarding Consumerâs Protection prohibits standardized contract if it creates harm to consumer. Bank Indonesia Regulation No. 11/11/PBI/2009 together with Bank Indonesia Circular Letter No. 11/10/DASP provide rights and obligations of the issuer in order to strengthen consumerâs protection. In many cases issuer gives the proxy to debt collector to collect over-due balance of credit card, and most of the time debt collector does the job improperly. With the recent death of credit card holder in Citibank Jakarta supposed to happen because of the guilty of debt collector, we are of the opinion that Bank Indonesia shoud review and strengthen all regulations regarding credit card business.